Cytosolic Delivery of Doxorubicin from Liposomes to Multidrug-Resistant Cancer Cells via Vaporization of Perfluorocarbon Droplets - Williams, Jacob B (2017)
A common mechanism of multidrug resistance is the upregulation of efflux pumps in the cancer cells that can more rapidly export unwanted materials (e.g. cancer drugs) out of the cell, compared to sensitive cancer cells. This research seeks to overcome this mechanism by vaporizing a perfluoropentane emulsion droplet inside of a drug-containing liposome (eLiposome) that was endocytosed into a cancer cell. Folate attached to the eLiposome facilitates uptake into the cell as observed by confocal microscopy. Ultrasound was examined as a trigger to initiate the vaporization of the perfluoropentane droplet and release doxorubicin from folated eLiposomes (feLD). Two seconds of ultrasound released 78% of encapsulated doxorubicin from feLD. Doxorubicin-sensitive KB-3-1 cells and doxorubicin-resistant KB-V1 cells treated with feLD (without ultrasound) had cell viabilities of 33% and 60%, respectively. Ultrasound had negligible additional effect on the cell viability of KB-3-1 and KB-V1 cells treated with feLD (33% and 53%, respectively). We hypothesized that the doxorubicin sulfate fibers that were formed during the loading of doxorubicin into the eLiposome present a site for heterogeneous nucleation once the feLD is endocytosed by the cell, and thus droplet vaporization occurs with or without ultrasound.